Human immunodeficiency virus epidemic scenery among brazilian women: a spatial analysis study - Ana Luisa Lemos Bezerra; Paula Regina Barbosa de Almeida; Renata Karina Reis; Glenda Roberta Oliveira Naiff Ferreira; Fabianne de Jesus Dias de Sousa; Elucir Gir; Eliã Pinheiro Botelho (BMC, 2023)
Abstract Background Approximately 37.7 million people worldwide are infected with human immunodeficiency virus (HIV). Although HIV detection among women, they still representing 53% of population living with the virus. Spatial analysis techniques are powerful tools for combating HIV allowing the association of the phenomenon with socioeconomic and political factors. Therefore, the main goal of this study was to spatially analyze HIV prevalence among Brazilian women from 2007 to 2020. Methods ecological study was conducted using secondary databases of the Notifiable Diseases Information System (SINAN) for HIV and Acquired Immunodeficiency Syndrom (AIDS) in Brazilian women 15 years old and over. Age-adjusted HIV/AIDS incidence rates were analyzed using spatial distribution, autocorrelation, and spatiotemporal risk analysis techniques. Results During the study period, 119,890 cases of HIV/AIDS were reported among Brazilian women. The southeastern region had a higher age-adjusted HIV/AIDS incidence than other Brazilian regions. Hotspot HIV/AIDS incidence rates decreased in all Brazil. Piauí, Paraná, and Minas Gerais were the only states with an increased number of cold spots. Previous spatiotemporal risk zones were observed in the states of São Paulo, Rio Grande do Sul, and Rio de Janeiro. Belém was a risk zone with a later spatiotemporal risk. Conclusions The efficiency of public policies fighting HIV has not been uniform among municipalities, although HIV/AIDS cases have decreased among Brazilian women. The social determinants of health in each municipality should be considered when local health authorities implement policies. Women empowerment should be promoted, and access to preventive, diagnostic, and treatment healthcare places should be expanded and guaranteed.